2015
DOI: 10.3390/mi6050574
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Polymer Lab-on-Chip Platforms for Ultrasonic Manipulation: Influence of the Substrate

Abstract: Abstract:The choice of substrate material in a chip that combines ultrasound with microfluidics for handling biological and synthetic microparticles can have a profound effect on the performance of the device. This is due to the high surface-to-volume ratio that exists within such small structures and acquires particular relevance in polymer-based resonators with 3D standing waves. This paper presents three chips developed to perform particle flow-through separation by ultrasound based on a polymeric SU-8 laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…According to their physical properties, several cultured pancreas cancer line cells TCs (Φ TC > 15 μm) were laterally entrained by the acoustic radiation force to reach the central node of pressure, keeping the smaller WBCs (Φ WBC ≤ 15 μm) flowing beside the channel walls at flow rate of 20 µL/min ≤ Q ≤ 100 µL/min and certain voltages supplied to the expectated piezoelectric ceramic. These results also agree with other studies in the literature reporting acoustic separation of TCs from WBCs [ 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…According to their physical properties, several cultured pancreas cancer line cells TCs (Φ TC > 15 μm) were laterally entrained by the acoustic radiation force to reach the central node of pressure, keeping the smaller WBCs (Φ WBC ≤ 15 μm) flowing beside the channel walls at flow rate of 20 µL/min ≤ Q ≤ 100 µL/min and certain voltages supplied to the expectated piezoelectric ceramic. These results also agree with other studies in the literature reporting acoustic separation of TCs from WBCs [ 35 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 93%
“…On the contrary, recently developed 3D chip resonators allow the use of structural materials of a low acoustic impedance and stiffness, such as polymers. These structures do not impose strict restrictions in the channel width, as reported previously by our group [ 30 , 37 ]. These devices are suitable for bio-applications due to their high bio-compatibility and low-cost manufacture.…”
Section: Introductionmentioning
confidence: 68%
“…Many theoretical studies of 3D standing waves have reported numerical solutions of the governing equations obtained using the COMSOL Multiphysics ® finite element software [19][20][21]. It has also been shown that the acoustophoretic particle motion can be modeled using numerical solutions of the equations of motion with code that includes iterative methods such as a fourth-order Runge-Kutta [22][23][24]. Such software solutions decrease calculation time, facilitate study and accurate prediction of the simultaneous acoustophoretic motion of many particles or cells, and can be used to model dynamics of the aggregation processes in resonant chambers and to optimize separation throughput in different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Simple mass-produced glass capillary tubes have been used for trapping of microparticles [2][3][4][5][6][7] and even nanoparticles [8,9]. The first attempts of using polymer-based devices have been published showing applications such as focusing of polymer beads [10][11][12][13], lipids [10], and red blood cells [11,14], as well as blood-bacteria separation [15] and purification of lymphocytes [16]. Although a cheaper material, polymers are difficult to use in acoustofluidics due to their low acoustic contrast relative to water, but recently it was shown how to circumvent this problem by use of the whole-system-resonance principle [17].…”
Section: Introductionmentioning
confidence: 99%